Pattern and Appropriateness of Antiemetic Drug Utilization in Breast Cancer Patients at Sultan Agung Islamic Hospital, Semarang, Indonesia - Sri Susilowati; Amelia Tivani Sari (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2026)
Chemotherapy-induced nausea and vomiting (CINV) are common adverse effects experienced by patients undergoing chemotherapy. Antiemetic therapy is a key strategy for the prevention and management of CINV; therefore, appropriate antiemetic use is essential. This study aimed to determine the patterns of chemotherapy and antiemetic utilization and to evaluate the appropriateness of antiemetic therapy based on the emetogenic risk of chemotherapy agents and antiemetic dosing standards in breast cancer patients at Sultan Agung Islamic Hospital, Semarang, Indonesia, in accordance with the National Comprehensive Cancer Network (NCCN) Guidelines 2024. The study was conducted observationally using a cross-sectional design with retrospective data collection from patients’ medical records. A total of 84 breast cancer patients were included through purposive sampling, according to predefined inclusion and exclusion criteria. The most frequently used chemotherapy regimen was paclitaxel–cisplatin (26%). Antiemetics were administered both prophylactically and post-chemotherapy, with ondansetron combined with dexamethasone as the most commonly used regimen (99.4%), along with ranitidine and diphenhydramine as adjunctive therapy. Evaluation of antiemetic appropriateness showed that 98.8% of patients did not receive antiemetic therapy consistent with the emetogenic risk of the chemotherapy agents, particularly among those receiving high-emetogenic-risk regimens. In addition, dose evaluation revealed inappropriate dexamethasone dosing, primarily due to underdosing and non-standard dosing frequency compared with the NCCN Guidelines 2024. Overall, antiemetic use was largely inconsistent with NCCN Guidelines 2024 recommendations, potentially compromising optimal CINV prevention in highly emetogenic chemotherapy.